CORRELATION BETWEEN MALOCCLUSION AND HISTORY OF BULLYING IN ADOLESCENTS AT MTSN 2 TANAH LAUT SOUTH KALIMANTAN - Widyandini Aulia Arif; Melisa Budipramana; Galuh Dwinta Sari; Muhammad Yanuar Ichrom Nahzi; Isnur Hatta (Dentin, 2024)
Background: Bullying in schools has been a source of concern for societies all over the world. The physical aspect is one of the triggers for bullying in adolescents. Assessment of these physical aspects; such as, weight, height, and facial appearance include the condition of the teeth. Moreover, prominent conditions of malocclusion; such as, gaps between teeth, crowding, overbite and overjet, are the most frequently reported targets by bullies. Purpose: To analyze the relationship between malocclusion and history of bullying in adolescents at MTsN 2 Tanah Laut South Kalimantan. Methods: Cross sectional research design is the methodology used in this observational analytical study. ICON was used to assess malocclusion severity and a validated questionnaire adapted from previous research was used to assess bullying history. In addition, the samples obtained were 86 respondents aged 12-14 years. Results: The highest frequency distribution in this study is malocclusion in the easy category based on ICON by 41 people (47.7%) and history of bullying in the category of bullying has not happened to the respondent in the last two months as many as 69 people (57.4%). A significant correlation was found in the results of the Spearman analysis test between malocclusion based on ICON and a history of bullying. Conclusion: Malocclusion and history of bullying in adolescents at MTsN 2 Tanah Laut South Kalimantan are correlated in a one-way manner, meaning that the severity of the malocclusion category increases in tandem with the history of bullying category.